Industrial Relations and the Industrial Revolution: Evidence from M'Connel and Kennedy, 1810–1840 - Huberman, Michael (Business History Review, 1991)
Using the record books of M'Connel and Kennedy, a leading cotton-spinning firm in Manchester, this article traces the development of managerial strategies to elicit effort from workers during the Industrial Revolution. Contrary to the conventional wisdom, the firm had difficulty in extracting effort from its workers, who were unwilling to increase output without capturing some of the gains through wage adjustments. Since spinners controlled the work organization, M'Connel and Kennedy had to accommodate workers' demands for stable piece rates, which were codified in the Manchester list of prices of 1829.